Consensus and contentious statements on the use of probiotics in clinical practice: A south east Asian gastro‐neuro motility association working team report. Issue 10 (12th June 2018) - Gwee, Kok‐Ann; Lee, Warren Wei‐Rhen; Ling, Khoon Lin; Ooi, Choon Jin; Quak, Seng Hock; Dan, Yock Young; Siah, Kewin Tien‐Ho; Huang, James Guoxian; Chua, Andrew Seng Boon; Hilmi, Ida Normiha; Raja Ali, Raja Affendi; Ong, Christina; et al.
Abstract: The concept of consuming microorganisms in the treatment of a medical condition and in health maintenance has gained much attraction, giving rise to an abundance of medical claims and of health supplements. This study identified relevant clinical questions on the therapeutic use of probiotics and reviewed the literature in irritable bowel syndrome, inflammatory bowel disease, impaired intestinal immunity, liver disease, intestinal infections, and common childhood digestive disorders. Statements were developed to address these clinical questions. A panel of experienced clinicians was tasked to critically evaluate and debate the available data. Both consensus and contentious statements are presented to provide to clinicians a perspective on the potential of probiotics and importantly their limitations.